2017
DOI: 10.1080/10934529.2017.1368300
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of phenol degrading bacterium strainBacillus thuringiensisJ20 from olive waste in Palestine

Abstract: This study aimed at isolation of phenol degrading bacteria from olive mill wastes in Palestine. The efficiency of phenol removal and factors affecting phenol degradation were investigated. A bacterial strain (J20) was isolated from solid olive mill waste and identified as Bacillus thuringiensis based on standard morphological, biochemical characteristics and 16SrRNA sequence analysis. The strain was able to grow in a phenol concentration of 700 mg/L as the sole carbon and energy source. The culture conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The result coincides with those of Ereqat et al. (2017), who have also found that the optimal temperature was 30°C for Bacillus thuringiensis J20, and increasing the temperature from 25°C to 30°C increases the percentage of degradation of phenol, ranging from 74.5% to 88.6%, while increasing the temperature above 30°C, the phenol degradation was about to decrease from 88.6% to 62.1%. Similarly, Shah (2018) recorded the temperature of 30°C as optimum for phenol removal of 78.69% by indigenous P. mendocina .…”
Section: Resultssupporting
confidence: 91%
“…The result coincides with those of Ereqat et al. (2017), who have also found that the optimal temperature was 30°C for Bacillus thuringiensis J20, and increasing the temperature from 25°C to 30°C increases the percentage of degradation of phenol, ranging from 74.5% to 88.6%, while increasing the temperature above 30°C, the phenol degradation was about to decrease from 88.6% to 62.1%. Similarly, Shah (2018) recorded the temperature of 30°C as optimum for phenol removal of 78.69% by indigenous P. mendocina .…”
Section: Resultssupporting
confidence: 91%
“…To our awareness, this is the initial study linked to biodegradation of the phenol compound by Curtobacterium. In fact, although the biodegradation of phenol compounds by microorganisms is argued exceedingly in the literature [16,24,25], no investigations involving Curtobacterium have been published. C. flaccumfaciens was capable to…”
Section: Substrate Concentration Effectmentioning
confidence: 99%
“…Although highly acclimatized to phenol, the bacteria showed an extended lag phase because of the high phenol concentration. Most of the studies pertaining to bacterial metabolism of phenol was aerobically performed, oxygen is used by the phenol hydroxylase enzyme for adding a second hydroxyl group [1,15,16]. During biodegradation of aromatic compounds as growth substrates they transformed to dihydroxy derivatives of either ortho or para before ring cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism with microorganisms is based on the change from oxidative state or complex to another state (valance transformation), volatilization, and extracellular chemical precipitation. [ 4–9 ] Bacteria are confessed as the most abundant microorganisms in the ecosystem with a high surface to volume ratio. [ 10 ] The bioremediation efficiency is depending not only on the ambient conditions, such as pH and temperature, but also to the type of bacteria.…”
Section: Introductionmentioning
confidence: 99%